2015
DOI: 10.1534/g3.114.016238
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Imprinted Gene Expression in Mouse Trophoblast Stem Cells

Abstract: Several hundred mammalian genes are expressed preferentially from one parental allele as the result of a process called genomic imprinting. Genomic imprinting is prevalent in extra-embryonic tissue, where it plays an essential role during development. Here, we profiled imprinted gene expression via RNA-Seq in a panel of six mouse trophoblast stem lines, which are ex vivo derivatives of a progenitor population that gives rise to the placental tissue of the mouse. We found evidence of imprinted expression for 48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 36 publications
2
38
0
Order By: Relevance
“…More recently, Calabrese et al . () suggested that Mas1 was a candidate imprinted gene, following detection of parent‐of‐origin biased expression (maternal allele) in trophoblastic stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Calabrese et al . () suggested that Mas1 was a candidate imprinted gene, following detection of parent‐of‐origin biased expression (maternal allele) in trophoblastic stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…Among the 135 genes, 53 corresponded to well-characterised imprinted genes in classic databases (33)(34)(35)(36). A further 17 of these genes, including Fkbp6, Smoc1/2, Gzmc/d/e/f/g, Zdhhc14 and Arid1b have been identified as imprinted in one or several recent studies (12)(13)(14)(15). The remaining 65 genes constitute novel candidate genes with parent-biased expression in mouse placenta.…”
Section: Methodsmentioning
confidence: 99%
“…Other novel secondary DMRs overlapped introns rather than transcriptional start sites. Park2, a recently identified maternally-biased gene (13), had seven intronic DMRs, all displaying hypermethylation of the maternal allele. Rian displayed a DMR that had not been previously reported in mice, although its human ortholog also presents an intronic imprinted DMR (45 Imprinted genes are much more frequently located within 100-100,000 bp of an imprinted DMR.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We next examined whether we could use CRISPR-Bac to activate and repress transcription of a lncRNA using dCas9-VP160 and dCas9-KRAB, respectively. We chose to target a lncRNA called Airn in two cell types: mouse ESCs, where Airn is naturally expressed at low levels, and mouse trophoblast stem cells (TSCs), where Airn is expressed and active ( (Andergassen et al, 2017;Calabrese et al, 2015;Latos et al, 2009); Figure 5A). In ESCs, we were able to activate Airn ~12-fold above its levels in non-targeting sgRNA control cells ( Figure 5B), but we were not able to repress Airn, likely due to its low endogenous expression (not shown; (Latos et al, 2009)).…”
Section: Activation and Repression Of Lncrna Transcription Using Crismentioning
confidence: 99%